Foreign body mimicking malignancy in acquired dacryocystocele - Mirza, Ahmad A. (Clin Case Rep, 2017)
A featured malignant‐like granulation tissue can be the only preoperative clinical clue of a concealed foreign body in the nasal cavity. Thus, endoscopic Dacryocystorhinostomy (DCR) should be completed with intraoperative nasal exploration to reveal non‐apparent foreign bodies that might be the underlying etiology of chronic dacryocystocele.